ANALISIS DISIPLIN KERJA PEGAWAI DAN LINGKUNGAN KERJA KANTOR KEPALA DESA BANJARSARI KECAMATAN CIAWI KABUPATEN BOGOR - Conie Nopinda Br Sitepu; Noni Yusnita Br Surbakti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to analyze and determine the Work Discipline and Work Environment. The data collection used is data obtained from interviews with Village Heads, Employees and the Community. The results of this study indicate that the work discipline of employees and the work environment of the Head Office of Banjarsari Village, Ciawi District, Bogor Regency is not good. This can be seen from the still existence of work discipline violations including there are several Banjarsari Village Head Office employees who come not according to the schedule. has been determined, some sometimes go home from work but have not arrived at the specified schedule, Not all employees carry out whatever the work rules are, some there are also employees who have not followed because the employee still has not applied his discipline such as being late for work, there are some The employees I saw wore sandals when there was no work or no residents came to take care of files. While the work environment is characterized by the presence of disturbing noise in the workplace and the room for government and service divisions is quite narrow because the workplace is combined and does not have a separate work space and the layout of the room and work desk is not in accordance with what is needed to support the work.